2014
DOI: 10.1371/journal.pone.0104945
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities among the HIV-Infected Patients Aged 40 Years or Older in Taiwan

Abstract: BackgroundWith the widespread use of combination antiretroviral therapy (cART), life expectancy of HIV-infected patients has significantly prolonged. An increasing number of HIV-infected patients are aging and concurrent use of medications are not uncommon for management of metabolic complications and cardiovascular diseases related to aging and prolonged exposure to cART.MethodsWe reviewed medical records of all HIV-infected patients aged 40 years or older who had been followed at a university hospital for HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 46 publications
7
24
1
Order By: Relevance
“…A quarter of the patients (median age 56 years) had two prescribed co‐treatments and more than half of the patients (56.2%) had more than two co‐treatments in addition to their cART. This confirms that the aging HIV‐infected population is burdened with comorbidities, as described previously in the SHCS population and in other HIV‐positive populations . The major comorbidity in our study was cardiovascular disease.…”
Section: Discussionsupporting
confidence: 91%
“…A quarter of the patients (median age 56 years) had two prescribed co‐treatments and more than half of the patients (56.2%) had more than two co‐treatments in addition to their cART. This confirms that the aging HIV‐infected population is burdened with comorbidities, as described previously in the SHCS population and in other HIV‐positive populations . The major comorbidity in our study was cardiovascular disease.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have provided evidence that PLWHIV with ageing-associated comorbidities may require additional pharmacologic interventions that can complicate therapeutic management [24][25][26][27]. Consistent with findings reported in the literature [9,22,28,29] older PLWHIV are taking more medications to treat comorbidities than younger PLWHIV, or similarly-aged HIV-uninfected patients.…”
Section: Resultssupporting
confidence: 60%
“…In this study, it was found that the vast majority (90%) of HIV-1infected patients aged 50 years and older had at least one NARC. This prevalence is particularly high when compared to cohort and cross-sectional studies from other regions, which have reported one or more NARC in 50-70% of older HIV patients (Hasse et al, 2011;Rodriguez-Penney et al, 2013;Torres et al, 2013;Wu et al, 2014). However, two surveys conducted in the USA showed a prevalence of NARC over 90% (Brennan, 2009;Balderson et al, 2013).…”
Section: Discussionmentioning
confidence: 91%